THE OPERATIVE CYSTOSCOPE WITH JOYSTICK CONTROL MECHANISM OF FLEXIBLE TOOLS INSERTED INTO THE URINARY BLADDER AND THE URETER - B. K. Komyakov; M. E. Topuzov; V. A. Zubarev; O. V. Stetsik (Вестник хирургии имени И.И. Грекова)
The authors developed an operative cystoscope with joystick control mechanism of ureter catheters and other flexible tools. This construction allowed control of flexible tools inserted into the bladder and the ureter in various directions, thus providing a necessary observation of the operative field at endoscopic operations on the bladder and ureter. This was one of the factors, which determined the operation success.